2018
DOI: 10.1002/ldr.3144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent sediment source shift after revegetation in the Loess Plateau of China: Implications from sediment fingerprinting in a small catchment

Abstract: As an important soil and water conversation endeavor, the 'Grain for Green' project launched by the Chinese Central Government almost doubled the vegetation cover on the Loess Plateau between 1999 and 2013. The corresponding vegetation restoration considerably diminished slope erosion throughout the Loess Plateau, although erosion in gullies remains poorly understood. In this paper, a composite fingerprinting approach was employed to assess the relative importance of the erosion of gully and slope soils within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Soil erosion in the Loess Plateau not only caused agricultural degradation and farmers' poverty, but also threatened the ecological security of the Yellow River Basin (Heerink, Bao, Li, Lu, & Feng, 2009; Jiao, Wang, Zhao, Wang, & Mu, 2014; Li et al, 2012; Sun et al, 2014). In the Loess Plateau, the goal of the GFG is to prevent the severe soil erosion and reduce the sediment content in the Yellow River (Wang, Fang, Shi, & Lu, 2018; Zhou, Gan, Shangguan, & Dong, 2009). The GFG has had positive and far‐reaching effects on the ecological environment and economic development in relevant regions over the past 20 years (Gao, Liu, Li, & Shi, 2020; Jia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Soil erosion in the Loess Plateau not only caused agricultural degradation and farmers' poverty, but also threatened the ecological security of the Yellow River Basin (Heerink, Bao, Li, Lu, & Feng, 2009; Jiao, Wang, Zhao, Wang, & Mu, 2014; Li et al, 2012; Sun et al, 2014). In the Loess Plateau, the goal of the GFG is to prevent the severe soil erosion and reduce the sediment content in the Yellow River (Wang, Fang, Shi, & Lu, 2018; Zhou, Gan, Shangguan, & Dong, 2009). The GFG has had positive and far‐reaching effects on the ecological environment and economic development in relevant regions over the past 20 years (Gao, Liu, Li, & Shi, 2020; Jia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The goodness of fit (GOF) can be used to verify whether the output of the mixing model is acceptable (Wang, Fang et al, 2018). Motha et al (2003) indicated that the output could be accepted when GOF > 80.0%.…”
Section: Methodsmentioning
confidence: 99%
“…Accelerated soil erosion is a serious environmental problem (Wang et al, 2018) affecting the physical, chemical and biological quality of land and water worldwide (Malhotra et al, 2018). Although fine-grained sediment is a naturally occurring material in river systems, providing a fundamental input for the development of river landscapes and their aquatic ecosystems (Frostick et al, 1984; Lisle, 1989), excessive fine-grained sediment delivery to, and accumulation within, river systems is one of the most pervasive causes of watercourse degradation worldwide (Gellis and Gorman Sanisaca, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although fine-grained sediment is a naturally occurring material in river systems, providing a fundamental input for the development of river landscapes and their aquatic ecosystems (Frostick et al, 1984; Lisle, 1989), excessive fine-grained sediment delivery to, and accumulation within, river systems is one of the most pervasive causes of watercourse degradation worldwide (Gellis and Gorman Sanisaca, 2018). In fact, since the 1980′s there has been growing concern in many countries over the off-site issues associated with accelerated soil erosion (Evans et al, 2017), including muddy floods and the related damage to properties (Boardman et al, 1996), increased operational and maintenance costs for potable water purification (Cashman et al, 2018; Owens et al, 2016), deformation of channel morphology (Cashman et al, 2018; Collins and Walling, 2007; Gellis and Gorman Sanisaca, 2018; Haddadchi et al, 2013; Zhou et al, 2016), the excessive destruction of the earth (Wang et al, 2018), the transfer and redistribution of nutrients and pollutants (Blake et al, 2018; Carter et al, 2003; Collins and Walling, 2007; Westrich and Förstner, 2007), and the harmful effects on aquatic biology (Jones et al, 2014, 2012; Kemp et al, 2011; Wilkes et al, 2019). Alongside these off-site impacts, a wide range of on-site problems also result from accelerated soil erosion and sediment mobilization including, amongst others, reductions in soil fertility and water holding capacity and reduced crop productivity (Nosrati, 2017; Tiecher et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation